Model Integratif Pendidikan Akhlak dalam Pemikiran Pendidikan Islam Klasik dan Modern: Telaah Literatur Berbasis Tazkiyah Fikr dan Ta'dib - Fatakhul Huda (Excelencia: Journal of Islamic Education & Management, 2025)
Recent moral issues among students—such as rising intolerance, verbal aggression, and decreasing social empathy—indicate the urgent need for a renewed and holistic approach to Islamic moral education. This study aims to formulate an integrative model of moral education by analyzing the ideas of Al-Ghazali, Ibn Miskawaih, Fazlur Rahman, and Syed Muhammad Naquib al-Attas. Employing a library research method, this study uses comparative analysis and thematic synthesis to connect classical and modern perspectives in a systematic manner. The findings reveal that Al-Ghazali and Ibn Miskawaih emphasize inner moral cultivation through spiritual purification, self-discipline, and habitual virtue formation. In contrast, Fazlur Rahman and al-Attas highlight rational moral reasoning, social consciousness, and the centrality of adab as an epistemological foundation for education. The synthesis of these ideas results in an integrative model of Islamic moral education built upon three core pillars: tazkiyah (spiritual refinement), fikr (ethical reasoning), and ta’dib (socially grounded moral conduct). This model provides a comprehensive framework that balances cognitive, affective, and psychomotor dimensions of student development. The study offers practical implications for strengthening the Islamic Religious Education (PAI) curriculum, particularly in designing learning strategies that foster moral awareness, reflective thinking, and socially responsible behavior. It also contributes theoretically to the epistemology of Islamic education through the integration of spiritual values, rationality, and social ethics.